'Global Warming is Real': Superstorm Sandy, Stevens and the SU+RE House. (3rd January 2018) - Nastasi, John
Abstract : With every new extreme‐weather event, climate change becomes harder to deny. When a notorious 2012 hurricane hit Hoboken, New Jersey, academic staff at the city's Stevens Institute of Technology quickly responded with impact studies and by instigating multi‐party dialogue to tackle the issues. The architectural faculty's efforts soon became focused around the SU+RE House, which was to be the winning entry for 2015 in the Solar Decathlon – a student competition to design, build and operate a solar‐powered house, run by the US Department of Energy every two years. Guest‐Editor and Stevens faculty memberJohn Nastasi sets out the project's background and explains how it serves as a new model for architectural teaching.